On the agglomeration tendency of carbonaceous fuels in fluidized beds. (1st October 2020) - Urciuolo, M.; Solimene, R.; Ammendola, P.; Krusch, S.; Scherer, V.; Salatino, P.; Chirone, R.; Senneca, O.
Abstract: Single particle pyrolysis and combustion experiments have been carried out in a lab scale fluidized bed reactor at temperatures of 600–850 °C. The behavior of three different fuels is compared: a bituminous coal (Auguste Victoria), a typical bitumen used in the cement industry, a carbon rich solid waste from the refinery industry, characterized by a very high content of metals. The bituminous coal and the refinery waste particles, during the pyrolysis stage, produce interesting carbon-sand aggregates. The outer shell of these aggregates is constituted by quartz sand particles embedded in a carbon matrix. The aggregates are hollow inside. The size of the cavity is comparable with that of the original coal particles, while the outer shell is larger. The increase of particle size due to aggregate formation slows down the combustion rate. For bitumen, no carbon-sand aggregates are observed. The relations between the fuel properties and aggregates formation are discussed, in particular the chemical composition and the pyrolysis kinetics are examined. It is concluded that heavy/tarry species formed in the early pyrolysis stages are most likely responsible for the capture of the sand particles and formation of aggregates.